2000
DOI: 10.1093/treephys/20.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic capacity in a central Amazonian rain forest

Abstract: The vertical profile in leaf photosynthetic capacity was investigated in a terra firme rain forest in central Amazonia. Measurements of photosynthesis were made on leaves at five levels in the canopy, and a model was fitted to describe photosynthetic capacity for each level. In addition, vertical profiles of photosynthetic photon flux density, leaf nitrogen concentration and specific leaf area were measured. The derived parameters for maximum rate of electron transport (J(max)) and maximum rate of carboxylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
151
3
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(179 citation statements)
references
References 33 publications
20
151
3
5
Order By: Relevance
“…10.8). In this analysis, it appears that h dominates the trend in D while irradiance moderates the absolute values, presumably caused by the increased light interception and photosynthetic capacity with increased height and subsequent reduction in p c (Ehleringer et al 1986;Carswell et al 2000;Lloyd et al 2009). While h is clearly a global driver of D, the impact of irradiance on D should vary globally as a function of ecosystem leaf area and subsequent light interception profiles (Campbell and Norman 1998;Parker et al 2002;Koch et al 2004).…”
Section: Irradiance and Heightmentioning
confidence: 84%
See 2 more Smart Citations
“…10.8). In this analysis, it appears that h dominates the trend in D while irradiance moderates the absolute values, presumably caused by the increased light interception and photosynthetic capacity with increased height and subsequent reduction in p c (Ehleringer et al 1986;Carswell et al 2000;Lloyd et al 2009). While h is clearly a global driver of D, the impact of irradiance on D should vary globally as a function of ecosystem leaf area and subsequent light interception profiles (Campbell and Norman 1998;Parker et al 2002;Koch et al 2004).…”
Section: Irradiance and Heightmentioning
confidence: 84%
“…Recycling of isotopically depleted canopy CO 2 should strengthen the gradient of D with h; however, field measurements have shown this effect to be relatively small (Lloyd et al 1996(Lloyd et al , 1997Brooks et al 1997a, b;Buchmann et al 1997a, b). Leaf nitrogen concentration per unit leaf area and photosynthetic capacity sometimes increase with height (and light availability) due to decreased leaf mass per area (e.g., Bond et al 1999;Carswell et al 2000;Barnard and Ryan 2003;Lloyd et al 2009), which could further strengthen the observed relationship of D to h. This has been frequently observed in angiosperms, high leaf area forests, and trees that have not reached their maximum heights. In contrast, studies on particularly tall trees often find that leaf nitrogen per unit mass and photosynthetic capacity do not vary or even decline with h (McDowell et al 2002a;Ambrose et al 2009;Woodruff et al 2009, Nothofagus data from this study).…”
Section: Why Does D Decline Linearly With Increasing H?mentioning
confidence: 87%
See 1 more Smart Citation
“…Differences in the C i /C a ratio among plant species have been attributed at least in part to variation in stomatal conductance to CO 2 (Ehleringer & Cerling,1995 (Carswell et al, 2000), indicating that the photosynthetic system of Ochroma was apparently little or not affected by the harsh environmental conditions of this degraded landscape.…”
Section: Gas Exchange and Electron-transportmentioning
confidence: 99%
“…Dentro dos ambientes fl orestais o acesso à luz é um dos principais fatores limitantes ao crescimento de espécies ar-bóreas (Carswell et al 2000;Felfi li et al 2001;Montgomery & Chazdon 2002). Florestas tropicais caracterizam-se pela presença de um estrato arbóreo desenvolvido que intercepta grande parte da irradiação solar incidente sobre a copa.…”
Section: Introductionunclassified